Social Investment Funds in Sweden: Status and Design Issues - Lars Hultkrantz; Elin Vimefall (Örebro University School of Business, 2016)
Long-term investments in individual and social human capital, such as preschool, school, family support, early-intervention for youth at risk and other programmes that are part of the welfare services provided by local government in Sweden are generally managed with one-year-ahead budget planning. Against criticism that the resulting resource allocation is biased by short-sightedness, silo mentality and risk aversion, more than a fifth of Swedish municipalities have in recent years established "social investment funds" for promoting investment and innovation views on such measures. This article provides a background on the motives and current status of these funds at the national level and describes in more detail the design and project funding in two cases. Two critical design issues are discussed; whether investment returns should be paid back to the fund and whether assessment should be made of other societal benefits than avoided costs.
Keywords: D61; D73; H53; I38; 330; social investments; investing in children; cost-benefit analysis